Strategies of Islamic education teachers in developing students’ basic life skills at SD IT Al Hijrah 2 - Nur Uswatun Hasanah; Rustam Rustam (International Journal on Education Insight, 2026)
This study aims to analyze students' basic life skills, identify the aspects of basic life skills developed at school, and describe the strategies used by Islamic Religious Education (PAI) teachers to improve students' basic life skills at SD IT Al Hijrah 2. This research employed a qualitative field research approach. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students' basic life skills developed in four aspects: personal skills, thinking skills, social skills, and vocational skills. These skills were developed through classroom learning, habituation programs, school culture, and extracurricular activities. The strategies implemented by PAI teachers included lectures, Problem-Based Learning (PBL), Discovery Learning, Inquiry Learning, Project-Based Learning (PJBL), discussions, role play, direct practice, modeling, and habituation. These strategies effectively supported the holistic development of students' life skills.